2017
DOI: 10.1089/dia.2017.0259
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Long-Distance Air Travel with Type 1 Diabetes

Abstract: We sought to determine the real-life experiences of individuals traveling long distance (across five or more time-zones) with type 1 diabetes (T1D). Five hundred three members of the T1D Exchange online community ( www.myglu.org ) completed a 45-question survey about their travel experiences flying long distance. The cohort was stratified by duration of T1D and whether or not participants used continuous subcutaneous insulin infusion (CSII) therapy and/or a continuous glucose monitor (CGM). In the last 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…The risk factors long-distance travel and use of medicinal plants were also maintained. According to Pinsker et al (2017), long-distance travel is a risk factor for unstable blood glucose in people with type 1 diabetes due to lack of information, presence of unfamiliar foods, time zone changes, inadequate insulin storage during the travel, among others. In addition, plants with mangiferin content, African walnut, kola biter, bitter leaf, cinnamon, turmeric, scent leaf, carob, and ginger can trigger glycemic changes (hypoglycemia and hyperglycemia) in people with diabetes (Ogunyinka, Oyinloye, Adenowo, & Kappo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors long-distance travel and use of medicinal plants were also maintained. According to Pinsker et al (2017), long-distance travel is a risk factor for unstable blood glucose in people with type 1 diabetes due to lack of information, presence of unfamiliar foods, time zone changes, inadequate insulin storage during the travel, among others. In addition, plants with mangiferin content, African walnut, kola biter, bitter leaf, cinnamon, turmeric, scent leaf, carob, and ginger can trigger glycemic changes (hypoglycemia and hyperglycemia) in people with diabetes (Ogunyinka, Oyinloye, Adenowo, & Kappo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The T1D Exchange Glu online community (myglu.org) includes a diverse group of people with T1D and caregivers, and provides a platform for meaningful research to amplify the collective voice of those living with T1D. [1][2][3][4][5][6] We present findings from a survey of the T1D Exchange Glu online community evaluating self-reported clinical outcomes and patient preferences impacting treatment choice in tubeless insulin pump users (Omnipod ® Insulin Management System, Insulet Corp., Acton, MA, United States) compared to their previous treatment. Eligibility criteria were age ≥18 years, T1D diagnosis ≥1 year, currently using Omnipod System for 0.5 to 2 years, and previously treated with multiple daily injections (MDI) or a tubed insulin pump.…”
Section: Letter To the Editormentioning
confidence: 99%
“…2,3 A number of studies have shown that the choice of travel destination by patients with diabetes may be affected by their use of insulin, and some of those patients avoid international travel altogether because of their disease. 4,5 While travelling, people with diabetes face many challenges that can affect their glycaemic control, including changes in their routines regarding diet and physical activity, and difficulties in adjusting insulin dose and timing after crossing multiple times zones, as well as the risk of infectious diseases, especially when travelling to developing countries. 5,6 Many travellers with diabetes are not aware of this health risk.…”
Section: Introductionmentioning
confidence: 99%